2015
DOI: 10.1161/circinterventions.115.002772
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Stent Placement for Iliofemoral Venous Outflow Obstruction

Abstract: Background-Endovenous recanalization of iliofemoral stenosis or occlusion with angioplasty and stent placement has been increasingly used to maintain long-term venous patency in patients with iliofemoral venous outflow obstruction. The purpose of this systematic review and meta-analysis was to determine safety and effectiveness of venous stent placement in patients with iliofemoral venous outflow obstruction. Methods and Results-We searched MEDLINE and EMBASE for studies evaluating safety or effectiveness of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(137 citation statements)
references
References 47 publications
6
117
0
4
Order By: Relevance
“…Furthermore, it is important to point out that the performers' degree of experience is elementary for a successful recanalization and a long-term patency rate, especially when treating complex cases such as these, requiring stenting of the iliocaval confl uence as in our second case [15,16]. Beside possible re-stenosis and persistence of symptoms, invasive treatment harbours a low risk of major bleeding from 0.3 -1.1 %, vessel perforation, compartment syndrome, pulmonary embolism from 0.2 % -0.9 %, periprocedural mortality from 0.1 % -0.7 %, stent fracture, and stent dislocation as well as early thrombosis from 1.0 % -6.8 % [3,11,14,17,18]. In addition, it is important to note that the radiation exposure increases with the complexity of the intervention, particularly in young patients undergoing interventions of the inferior vena cava plus both iliac veins, radiation exposures needs to be considered.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore, it is important to point out that the performers' degree of experience is elementary for a successful recanalization and a long-term patency rate, especially when treating complex cases such as these, requiring stenting of the iliocaval confl uence as in our second case [15,16]. Beside possible re-stenosis and persistence of symptoms, invasive treatment harbours a low risk of major bleeding from 0.3 -1.1 %, vessel perforation, compartment syndrome, pulmonary embolism from 0.2 % -0.9 %, periprocedural mortality from 0.1 % -0.7 %, stent fracture, and stent dislocation as well as early thrombosis from 1.0 % -6.8 % [3,11,14,17,18]. In addition, it is important to note that the radiation exposure increases with the complexity of the intervention, particularly in young patients undergoing interventions of the inferior vena cava plus both iliac veins, radiation exposures needs to be considered.…”
Section: Discussionmentioning
confidence: 70%
“…Recently published data by Stuck et al underline the excellent sustained patency; primary and secondary patency rates were 92% and 100% at six months [13]. A meta-analysis of Razavi et al reported a high technical success rate, depending on the cause of obstruction: For a total of 2,869 patients out of 37 studies, 12 months primary and secondary patency for chronic post-thrombotic disease pathogenesis was 79 % and 94 %, respectively [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In our study, 7 of 9 patients with procedural success (78%) were treated only with ballooning, whereas the remaining 2 patients (12%) received a stent and showed vein patency at 6 months post-intervention. Neglen et al reported 5-year stent patency rates of 67%.…”
Section: Grants / Conflict Of Interest / Acknowledgmentsmentioning
confidence: 62%
“…In this journal alone, for example, 13 meta-analyses were published between 2013 and 2015, and 7 of the 112 original articles that appeared in 2015 fell into this category. [1][2][3][4][5][6][7] Given the proliferation of such studies, in this journal and in the field more broadly, it seems an opportune moment to reflect briefly on their place in the evolving literature on structural interventions.…”
mentioning
confidence: 99%